The Analysis Of Lecturer Knowledge For Implementation To The Effective Classroom - Meita Maharani (Jurnal Penelitian)
The purpose of this study was to implementation lecturers’ knowledge about effective classroom and their classroom practices for teaching English. It was also knowing the correspondence between lecturers’ knowledge and the practices. This study designed using qualitative case study approach. The data was obtained using multiple-choice typed test, observation checklist, and interview. The subjects were four English lecturers and their cadets as supporting subject. The data obtained was analyzed using interactive model proposed by Miles and Huberman. The data revealed that the subjects had variety of knowledge about classroom ; one of them had sufficient knowledge , another one showed average result and the other two were emerging. In their classroom practice, two lecturers performed effective classroom skill, but the other two showed average effort in managing their class. For the correspondence, it was found that there were three group of lecturers; the first group has sufficient knowledge and applied it simultaneously, the second group has average knowledge but applied it in more effective ways, and the third group has emerging knowledge and applied it likely to be the same as their knowledge in the classroom practice.